Efficacy of Intravenous Dexamethasone and Placebo in Postop Sore Throat Prevention after Oral Endotracheal Intubation - Mahendar, Udesh Kumar, Kainat, Ravi Kumar, Rajesh, Ajeet Kumar, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the efficacy of intravenous dexamethasone with placebo in preventing POST after endotracheal intubation in general surgical patients. Design: Randomized controlled trial. Place and duration of study: Department of Anesthesiology and Surgical Intensive Care Unit and Pain Management, Civil Hospital, Dow University of Health Sciences Karachi from 12th January 2015 to 11th July 2015. Methodology: Sixty six patients underwent elective surgical procedures with tracheal intubation were included. Patients were randomly divided in Group A treated with dexamethasone and Group B treated with normal saline. Anesthesia was induced 5 minutes later. Tracheal intubation was performed after ensuring maximum neuromuscular blocking affect. At the end of the 24 hours after surgery POST was evaluated by VAS. Results: Thirty seven (56.1%) were males and 29(43.9%) were females. Efficacy was significantly high in group A as compare to group B (84.4% vs. 33.3%; p=0.0005]. Conclusion: Prophylactic intravenous administration of dexamethasone was associated with a statistically significant reduction in the incidence of POST after tracheal extubation. Keywords: Sore throat, Dexamethasone, Endotracheal intubation, General surgical